Nigerian students' preceived challenges in the provision of qualitative secondary education in the 21st Century. (2011)
Education is a vehicle for effecting socio-political and economic change. As such, there is no need to employ cost-effective and efficient measures in its implementation process to ensure quality provison. The present study examined the provision of education from the perspective of undergraduate students using Focus Group Discussion (FGD) method, and qualitative analysis to present issues raised at the interractive sessions. The subjects were drawn from four basic faculties ( Basic Science, Education, Social Sciences and Arts) of the University of Ibadan, Nigeria. The findings revealed that the average Nigerian undergraduate would want to see the provision of a comprehensive secondary education that seeks to develop the cognitive, affective and skill development in the individual. Such provision of education has implication for proper training and retraining of teachers, who are well groomed in the art of pedagory, child psychology and counselling. The role of government, school managers and parents,as well as other stakeholders in this process of providing qualitative education in the country were well highlighted in the study.